Strategi Promosi Wisata Goa Lia Balano Berbasis Media Online Pemerintah Desa Lauwon Kecamatan Luwuk Timur Kabupaten Banggai - Magfira Ladupu; Falimu (Yayasan Literasi Sains Indonesia, 2022)
This study aims to determine the online media-based tourism promotion strategy by the village government. The analytical method used in the implementation of the research is observation, interviews and documentation. Data analysis was carried out through qualitative descriptive. The results of the research conducted that online media can improvetotaltourists to be able to visit both local tourists and foreign tourists. Promotion strategies using online media, activity events and improvement of tourist facilities carried out by the village government are expected to attract tourists and of course improve the economy of the community around these tourist attractions.